Kontribusi Strength Based Parenting dan Academic Self-Efficacy terhadap Engagement pada Siswa SD Mutiara Harapan Pangkalan Kerinci Riau - Batubara, Ellen Ester; Rohinsa, Meilani; Setiawan, Tery (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2024)
This study aims to investigate the contributions of Strength-Based Parenting and Academic Self-Efficacy to the level of engagement among students at SD Mutiara Harapan Pangkalan Kerinci Riau. Strength-Based Parenting is an approach to parenting that focuses on developing a child's strengths and potential, while Academic Self-Efficacy refers to an individual's belief in his ability to face academic tasks. This study used a quantitative approach involving 102 students of SD Mutiara Harapan as the research participants. Data was obtained through a questionnaire that measured the level of Strength-Based Parenting, Academic Self-Efficacy, and student engagement. Data analysis was performed using regression techniques to examine the relationship between the variables studied. The results showed that Strength-Based Parenting and Academic Self-Efficacy significantly contributed to the level of engagement of SD Mutiara Harapan students. The higher the level of Strength-Based Parenting received by students and the higher the Academic Self-Efficacy that students have, the level of student engagement tends to increase. This research makes an important contribution to understanding the factors that influence engagement in elementary students, especially in the context of using the Strength-Based Parenting approach and developing Academic Self-Efficacy. The results of this study can provide practical guidance for parents and educators in strengthening student engagement through positive parenting approaches and building academic self-confidence.